IMPACT THE MANAGEMENT IMPLEMENTATION LEVELS ON SME. PERFORMANCE - MyoHtike, Zin (International Journal of Psychosocial Rehabilitation, 2020)
-SME.have required management coordinate, align resources and actions with mission. The study examines performance impact from management adopted planning to achieved and enhance changes in business environment.SME. defined economic development on microeconomic stability, dependable on planning and implementation.The research measured the implementation had well perform in SME. by the methods of in- depth interview to mid and top-levels management recommend accordingly. This study found that the different types of management and implementation in SMEs., some of business do not well in management and implementation even researcher face the limitation strictly for this collection. Managing business operates as standards in all clients, customers, suppliers, environment and the communities to processes able to take into action. SMEs. in business prove that an efficient, effective implementation can increased revenues also develop performance of organization